Terengganu cultural trail: using videography in a participant-observer study to enhance cultural heritage appreciation among children / Siti Hajar Abd Aziz … [et al.] - Abd Aziz, Siti Hajar; Ahmad Ridzuan, Ahmad Nur Azam; Mohd Azni, Zuliani; Khamis, Muhamad Hanapi; Abu Bakar, Norida (UiTM Cawangan Melaka Kampus Jasin, 2021)
With the new technological improvements, video-based observation research is becoming a promising method in many areas. Video recording has been under-utilized as a data collection tool because of confidentiality and privacy issues. However, it has many benefits as opposed to traditional observations, and recent studies using video recording methods have introduced new research areas and approaches. This paper aimed to describe the videography project in a participant-observer study to enhance cultural heritage appreciation among children. This project attempted to record children’s experiences in Terengganu culture showcase which was in conjunction with the Terengganu Cultural Village which took place at various events in Kuala Terengganu in September 2020. It is also hoped to give some insights about children’s appreciation of Terengganu cultural heritage when videography was incorporated as its observation tool. The researchers hoped to nurture active learning in an early age, and this includes a cultural appreciation for the participants. Participants embarked on a three-day journey to experience the cultural heritage of the mystical Terengganu, where silat, gasing and wayang kulit were popular but unknown to the participants. It hopes to nurture cultural appreciation where participants seek to understand and learn about Terengganu cultural heritage in an effort to broaden their perspective and connect with others.